A Politics of Indifference: Reading Cavarero, Rancière and Arendt. Issue 2 (July 2019) - Huzar, Timothy J.
Abstract : This article compares the accounts of politics found in the work of Adriana Cavarero and Jacques Rancière. It argues that when Cavarero offers a formal account of politics she thinks politics with Hannah Arendt and thus falls foul of Rancière's critique of Arendt. However, Cavarero offers the sense of another account of politics in her reading of Penelope in In Spite of Plato, one that not only avoids Rancière's critique but demonstrates the limits of Rancière's own account of politics. Cavarero makes tangible a sense of a politics indifferent to extant orders, something that is difficult to discern in Rancière given his insistence that politics makes visible forms of existence that could not otherwise be seen, said or heard.